High-performance photodetector from p-n junction of vertically aligned SnS2 and reduced graphene oxide - Das, Chayan; Kumar, Suresh; Dambhare, Neha V.; Kumar, Mahesh; Rath, Arup K.; Sahu, Satyajit (ACS Applied Electronic Materials, 2024)
Semiconducting 2D transition metal dichalcogenides (TMDC) became very popular in photodetection due to their high mobility and high rate of generating electron and hole pairs. Over the past decade, MoS2 and WS2 became the most popular TMDC for several applications. On the other hand, due to the complex synthesis process compared to MoS2 and WS2, SnS2 became a less popular 2D material for photodetection. We synthesized vertically aligned SnS2 flakes by a chemical vapor deposition (CVD) process with three temperature zones with controlled argon (Ar) gas flow. Pristine SnS2-based devices are not very suitable for photodetection applications because of their low photo-to-dark current ratio (I ph /I (dark) ), high response time, and low stability. So, they need to be decorated with oppositely doped materials. We decorated pristine SnS2-based devices with rGO nanoparticles, which significantly increased the device's performance. We found a high responsivity (R) of 1.33 A/W, detectivity (D) of 6.95 x 10(11) Jones, I ph /I dark of 102, and a rise time of 0.241 ms (fall time of 1.318 ms) with the rGO decorated SnS2-based device.
Keywords: 2D-SnS2; CVD; p-njunction; photodetector; rGO

WS2 nanoparticle-decorated, vertically aligned SnS2-based high-performance heterostructures for ambient-stable ultrafast photodetection - Das, Chayan; Kumar, Suresh; Sharma, Anjali; Kumar, Mahesh; Rath, Arup K.; Sahu, Satyajit (ACS Applied Nano Materials, 2025)
The development of visible-light photodetectors with high responsivity, rapid response, and long-term ambient stability remains a critical challenge in optoelectronics. Here, we report a high-performance photodetector based on a vertically aligned SnS2 film interfaced with WS2 nanoparticles, forming a p-n heterojunction. This device is fabricated using a scalable two-step method-chemical vapor deposition (CVD) for SnS2 growth and solution-based drop-casting for WS2 deposition-enabling precise control over the heterointerface, but trap states are inevitable due to the use of thermal CVD and the drop-casting method. The resulting photodetector exhibits remarkable optoelectronic characteristics, including a responsivity of 0.76 A/W, a detectivity of 7.56 x 10(11) Jones, a photo-to-dark current ratio of 119, and a fast rise time of 0.297 ms under visible illumination. These performance metrics are directly attributed to the optimized heterointerface, where the built-in electric field at the nanoscale WS2/SnS2 junctions promotes efficient charge separation and minimizes recombination losses. Notably, the device retains over 95% of its initial performance even after 1 week of ambient exposure, highlighting its superior environmental robustness. This work introduces an interface-engineering strategy that leverages the unique electronic properties of earth-abundant, nontoxic two-dimensional materials, offering a viable pathway for scalable, high-speed, and stable photodetectors suitable for next-generation optoelectronic systems.
Keywords: 2D; CVD; heterojunction; photodetector; SnS2; WS2